MOBILIZING VOTERS THROUGH POLITICAL COMMUNICATION: THE ROLE OF PKS IN THE 2024 SOUTHEAST ACEH ELECTION - Irfan Syah Putra; Rubino Rubino; Erwan Effendi (International Journal of Cultural and Social Science, 2025)
This study aims to analyze the political communication conducted by the Regional Leadership Council (DPD) of the Prosperous Justice Party (PKS) in gaining public support during the 2024 General Election in Southeast Aceh Regency. The research focuses on the strategies, forms, and media of political communication used by the DPD PKS, as well as the supporting and inhibiting factors in the process. A qualitative approach with a case study method was employed. Data were collected through in-depth interviews with DPD PKS administrators, observation of party political activities, and documentation from various relevant sources. The findings indicate that the Southeast Aceh DPD PKS prioritizes political communication based on Islamic values, social services, and personal closeness with the community. Communication strategies are implemented through social media, face-to-face meetings, regular religious gatherings (pengajian), and community service activities. The success of this communication is supported by the party’s religious image and cadre solidarity; however, it also faces challenges such as limited media access, low political literacy among some segments of the population, and intense inter-party competition in the region. The study concludes that the effectiveness of DPD PKS's political communication in gaining support for the 2024 election is largely determined by its ability to build trust, maintain message consistency, and apply direct approaches to the public. The study recommends enhancing the communication capacity of party cadres and optimizing the use of digital technology to better reach young voters.